On sequential confidence interval in a stationary Gaussian process. Issue 4 (2nd October 2021) - Sarkar, Pritam; Bandyopadhyay, Uttam
Abstract: In this article we concentrate on fixed accuracy intervals of the common variance when the data arise from a Gaussian process with order 1 autoregressive covariance structure. Our approach includes the maximum likelihood method and least squares method for estimating the parameters in this process. We provide necessary asymptotic results and carry out numerical evaluations.